Reflections in the Waves: What Interreligious Studies Can Learn from the Evolution of Women's Movements in the U.S - Mikva, Rachel S. (Journal of ecumenical studies, 2018)
As colleges, universities, and seminaries innovate programs in Interreligious Studies while the academic field is just taking shape, Women's Studies and now Gender Studies provide fruitful models for analysis. The fields share a critical mix of theory and praxis, a commitment to seek understanding across lines of difference, contemporary relevance, and intersectional and interdisciplinary complexity. Using the "waves" of women's movements as a mirror, the essay discusses sequential but not separate developments that emphasize equality, difference, diversity, and intersubjectivity. This lens sharpens our view of the learning curve for Interreligious Studies and Engagement and illuminates some future directions for the field.